PENGARUH KENAIKAN HARGA BBM TERHADAP TARIF BUS TRANS METRO BANDUNG (KORIDOR II JURUSAN CICAHEUM-CIBEUREUM) - Elkhasnet, Elkhasnet; Hura, Antonius (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
The fuel prices increase affects the overall economic and also affects the public transport fares. The increase in public transport fares shall be balance with the increase in fuel prices so that the vehicle’s operating cost that incurred by the operators in line with ability to pay of public transport passengers. The aim of this study is to determine the effect of fuel price on Trans Metro Bandung bus fare particular for Cibeureum-Cicaheum route. Vehicle’s operating cost and fares are calculated in two times; before and after the fuel prices increase. The study obtained that the component percentage before the fuel price increase is 15.89% of BOK while after the fuel price increase is 20.94% of BOK. According to fares calculation, the fares increase from Rp. 3.500 per passenger to Rp. 4.000 per passenger, meanwhile, in reality, the operators set the price at Rp. 3.000 per passenger before and after the fuel prices increase.